Interpretation of Nitrogen Isotope Profiles in Petroleum Systems: A Review - Quan, Tracy M.; Adeboye, Oyeleye O. (Frontiers in Earth Science, 2021)
Bulk sedimentary nitrogen isotope profiles are often used as proxies for depositional redox conditions, nitrogen cycling, and nutrient uptake in modern and ancient marine systems. The general preference in terms of analysis is that the sediments measured have undergone minimal thermal alteration, as post-depositional processes might have altered the initial d15N signal, thus complicating the interpretation of these records. Although not a traditional proxy for petroleum evaluation purposes, recently the use of nitrogen isotopes in petroleum systems has been investigated as potential proxies to reconstruct paleoenvironmental conditions such as redox, and for organic matter evaluation. In this paper we review the use of nitrogen isotope data in petroleum systems, their interpretations, and factors that may complicate their use as proxies. We review the evidence for nitrogen isotopic fractionation during diagenesis, catagenesis, and fluid migration as determined by lab experiments, and how these might impact interpretation of d15N data in petroleum systems. We also analyze the use and interpretation of d15N data from petroleum-producing reservoir units, including unconventional reservoirs and lacustrine basins. Lastly, we discuss potential applications for nitrogen isotopes in petroleum systems with regards to their use as both geochemical proxies and as tools to evaluate petroleum reservoirs.